PENGAKUAN NEGARA TERHADAP HAK-HAK POLITIK (RIGHT TO VOTE) MASYARAKAT ADAT DALAM PELAKSANAAN PEMILIHAN UMUM (Studi Putusan Mahkamah Konstitusi No.47-81/PHPU.A-VII/2009) - Zazili, Ahmad (Mahkamah Konstitusi Republik Indonesia, 2012)
Constitutional right is basic right for all Indonesian people, not least for indigenous people which still uphold the values of their customary law. Customary law is often different from the positive law in Indonesia, but it’s not a reason to deny the customary law on indigenous people in a region. One of the Indigenous people is in Yahukimo where the community uses their customary law in various patterns of life. Therefore, even in the election they use their own customary law and are not guided by the Election Law. Noken is the way they cast a vote. Constitutionality of Noken is accepted as a cultural value by the Constitutional Court.